A simplified spectrophotometric method for routine analysis of saccharin in commercial noncaloric sweeteners - Los Weinert, Patrícia [UNESP]; Redigolo Pezza, Helena [UNESP]; Oliveira, Jose Eduardo de [UNESP]; Pezza, Leonardo [UNESP] (American Chemical Society (ACS), 2004)
A simple, rapid, and sensitive spectrophotometric method for routine analysis of saccharin in commercial noncaloric sweeteners is proposed. This method is based on the reaction of saccharin with tetrachloro-p-benzoquinone (p-chloranil) accelerated by hydrogen peroxide and conducted in an ethanol:acetone (4:1) medium, producing a violet-red compound (γ max = 550 nm). Beer's law is obeyed in a concentration range of 2.05 × 10 -4 to 3.00 × 10 -3 M with an excellent correlation coefficient (r = 0.9998). The detection limit was 1.55 × 10 -5 M, and the effect of interferences on the spectrophotometric measurements was evaluated. The proposed procedure was applied successfully to the determination of saccharin in noncaloric sweeteners. Recoveries were within 99.2-104.3% with standard deviations ranging from to 0.5-1.6%. Results of the proposed method compare very favorably with those given by the high-performance liquid chromatography method recommended by the Food and Drug Administration.
Keywords: Noncaloric sweeteners; Saccharin; Spectrophotometric determination; 4 chloroaniline; acetone; alcohol; hydrogen peroxide; saccharin; sweetening agent; absorption; chemical reaction; concentration (parameters); correlation coefficient; high performance liquid chromatography; intermethod comparison; molecular interaction; reaction analysis; reaction time; reliability; spectrophotometry; Chloranil; Hydrogen Peroxide; Indicators and Reagents; Sensitivity and Specificity; Spectrophotometry; Sweetening Agents; Viola (angiosperm)